Assessment of Pollution Load in Marble Waste Water in Khairabad, District Nowshera, Khyber Pukhtunkhwa, Pakistan : Assessment of Pollution Load in Marble Waste Water in Khairabad, District Nowshera, Khyber Pukhtunkhwa, Pakistan - Said Akbar Khan; Muhammad Suleman; Maheen Asad (International Journal of Economic and Environmental Geology, 2017)
The current research was conducted to investigate pollution load in marble wastewater of marble industries in Khairabad, District Nowshera, Khyber Pakhtunkhwa, Pakistan. These marble industries dispose their wastes directly into the river Kabul passing through Jehangira and Khairabad, District Nowshera. For this purpose water samples were collected from selected locations of the marble industries along the length of river Kabul. Physical parameters like pH, temperature and electrical conductivity were analyzed on the spot, while Total Suspended Solids and Total Dissolved Solids were analyzed in laboratory using standard methods. Heavy metals were analyzed by using Atomic Absorption Spectrophotometer. The results were compared with Pakistan Environmental Protection Agency (Pak-EPA) and concluded that some of the parameters were within the safe limits of PAK-EPA, but the heavy metals concentrations were very high and thus affect water resources, if not adequately and properly managed. Moreover, the concerned sectors should regularly monitor the marble factories. Keywords: Wastewater, physicochemical parameters, heavy metals, Pak-EPA.